Influencing up - Cohen, Allan R. (Wiley, 2012)
"The authors of the classic Influence Without Authority explain the unique challenges of influencing powerful peopleLearn to overcome your difficulties with a boss who is uninterested in your concerns, or resistant to giving needed support. Or discover how to win the cooperation of senior managers who are hard to reach, and hard to sell on your ideas, products, or services. In their classic book, Influence Without Authority, Allan Cohen and David Bradford provided a universal model of how to influence someone you don't control. Influencing Up applies those ideas to problematic bosses and other powerful people, with sophisticated tactics for building partnerships with them. If you're afraid of retaliation or just unclear as to how to change a senior person's behavior, don't stay paralyzed. Influencing Up gives you the tools to bridge the power gap. Offers practical advice about how to turn your relationship with your boss into a partnership in which both parties benefit Explains what powerful people care about Shows how to overcome power gaps by developing more partner-like relationships Learn what a great partnership with your boss can do for your career--and your mental health!"--